Edukasi Masyarakat Mengenai Gejala Cemas - Resti Rahmadika Akbar; Mutiara Anissa; Insil Pendri Hariyani; Rhandyka Rafli (Universitas Lancang Kuning, 2022)
In the last two years, society has been faced with a global problem, namely a pandemic, which is related to various aspects of life. Daily life and work are affected by these circumstances. Mental health, especially anxiety, stress and even depression can be felt by the community. For this reason, by providing education about symptoms of anxiety, it is hoped that the community will be aware and be able to determine when to ask for help and self-management so that the functions of daily life are not disrupted. For this reason, by providing education about symptoms of anxiety, it is hoped that the community will be aware of and be able to determine when to ask for help and self-management so that the functions of daily life are not disrupted.